Adherence to the treatment of caregivers of children with Autism Spectrum Disorder (European Journal of Child Development, Education and Psychopathology, 2019)
The study focuses on the adherence to treatment of the family of the child with Autism Spectrum Disorder (ASD) or suspected diagnosis, identifying the elements that justify the adherence process. From that identification, develop a scale of measurement for its study. For this, adherence was evaluated with the application of a survey in a group of 128 parents of children with ASD and with suspected diagnosis, considering as variables: social, economic, family and individual factors. The results show the importance of the relationship of these factors with adherence in the adaptation to ASD such as: social support, life satisfaction and family cohesion.